A new fuel cell powered aerospace propulsion system / Thomas Arthur Ward … [et al.] - Thomas, Arthur Ward; Ow, Chee Sheng; Kuntjoro, Wahyu; Omar, Ahmad Maliki; Wahab, Nor'aini (Research Management Institute (RMI), 2010)
A fuel cell powered unmanned air vehicle (UAV) named Kenyalang-1 ("Hornbill") was designed, built, and flight-tested at the Universiti Teknologi MARA (UiTM) in Shah Alam, Malaysia. The project was funding under a grant from the Malaysian Ministry of Science, Technology, and Innovation (MOSTI). The UAV is propeller-driven by a DC brushless motor, powered by a 500 W proton exchange membrane (PEM) hydrogen fuel cell. The objective was to demonstrate the design and technological challenges involved and determine the relative merits or shortcomings that fuel cell electrically-powered propulsion systems have over conventional systems. This final project report describes the UAV design and power plant's performance. The results of this analysis will be used to improve the UAV and power plant system for future research and production models.